2020
DOI: 10.1111/sjop.12672
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an ACT‐based rehabilitation program for the treatment of chronic fatigue: Results from a 12‐months longitudinal study

Abstract: Acceptance and Commitment Therapy (ACT) is potentially effective for treating chronic fatigue. Given the paucity of studies on this topic, we aimed to assess long‐term trajectories of primary (fatigue, quality of life and functional abilities) and secondary outcomes (anxious and depressive symptoms) of an ACT‐based rehabilitation program for patients with chronic fatigue. Further, we examined if changes in potential process variables (psychological inflexibility, metacognitive beliefs, and cognitive and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…ACT considers cognitive fusion as a key feature of psychological inflexibility (Hayes et al, 2006), and the two are inextricably linked. A recent longitudinal study in ACT demonstrated that a correlation between mental fatigue and psychological inflexibility (Brugnera et al, 2021). Also, mental fatigue leads to reduced cognitive control and is more likely to trigger cognitive fusion (Bramwell & Richardson, 2018).…”
Section: The Chain Mediating Role Of Psychological Inflexibility and ...mentioning
confidence: 99%
“…ACT considers cognitive fusion as a key feature of psychological inflexibility (Hayes et al, 2006), and the two are inextricably linked. A recent longitudinal study in ACT demonstrated that a correlation between mental fatigue and psychological inflexibility (Brugnera et al, 2021). Also, mental fatigue leads to reduced cognitive control and is more likely to trigger cognitive fusion (Bramwell & Richardson, 2018).…”
Section: The Chain Mediating Role Of Psychological Inflexibility and ...mentioning
confidence: 99%
“…Thastum et al developed a treatment strategy in chronic post-concussion syndrome applying the idea of negative illness perception and maladaptive illness behaviour intended to break the vicious circles of excessive rest due to fatigue by gradually changing attitudes and slowly increasing participation in daily activities [ 43 ]. Likewise, cognitive behavioural therapy, graded exercise therapy, and acceptance and commitment therapy has been employed to treat mental fatigue syndrome and fatigue in chronic pain syndromes [ 7 , 8 , 21 , 38 ]. Hence, in order to develop similar behavioural therapy approaches customized for post-aSAH fatigue, knowledge of applied coping strategies in that group of patients would be crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Since ACT implies that you are trained to commit to face problems head-on rather than to avoid them, education according to ACT in psychiatric and pain related concerns could potentially reduce the requirement for sick leave. Indeed, several earlier trials have successfully employed ACT in clinical trials [16][17][18][19][20] some of which reduced sick leave prescription [16,18]. However, to the best of our knowledge, all previous studies of ACT to reduce sick leave in primary care were designed to treat the individual patients.…”
Section: Introductionmentioning
confidence: 99%